2021
DOI: 10.21203/rs.3.rs-637985/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

National COVID-19 Hospital Admissions and Mortality Among Healthcare Workers in South Africa, 2020-2021

Abstract: Background: Healthcare workers (HCWs) in close contact with SARS-CoV-2-infected patients have an increased risk of infection compared to non-HCWs, but little is known about the clinical course and risks for mortality amongst HCWs in South Africa. In this study, we compared characteristics of hospitalised HCWs with non-HCWs with COVID-19 and assessed factors associated with COVID-19 mortality among HCWs. Methods: Data from 5 March 2020 to 30 April 2021 was obtained from DATCOV, the national surveillance program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…A higher proportion of HCW cases is not unexpected, as the study by Gomez-Ochoa and colleagues showed a higher prevalence of SARS-CoV-2 infection among HCWs compared with the data from the general population [16]. Similar to reports on HCWs in South Africa, where more cases and increased COVID-19 hospital mortality were seen [9,17]. Compared to the epidemic curve among the population in SA, the epidemic curve comprising COVID-19 cases reported on OHASIS showed two waves (Fig 1).…”
Section: Plos Onesupporting
confidence: 64%
See 3 more Smart Citations
“…A higher proportion of HCW cases is not unexpected, as the study by Gomez-Ochoa and colleagues showed a higher prevalence of SARS-CoV-2 infection among HCWs compared with the data from the general population [16]. Similar to reports on HCWs in South Africa, where more cases and increased COVID-19 hospital mortality were seen [9,17]. Compared to the epidemic curve among the population in SA, the epidemic curve comprising COVID-19 cases reported on OHASIS showed two waves (Fig 1).…”
Section: Plos Onesupporting
confidence: 64%
“…A similar decrease in COVID-19 cases among medical laboratory services staff was seen in the second wave. This was thought to be due to reasons including improved safety protocols being implemented in health facilities, availability and appropriate use of PPE, better infection control measures being put into place, as well as improved handling of admitted patients [9]. In addition, previous exposure to COVID-19 has been shown to result in subsequently improved immunity against infections, which may also be the reason for a reduced number of cases in the second wave [18].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…Apart from studies among health workers (HWs) and reports among miners, there have been no studies on work-related COVID-19 in other groups of South African workers. [9][10][11][12][13][14]…”
Section: Work-related Covid-19 In South Africamentioning
confidence: 99%